P281 In vitro evaluation of the response of human tendon-derived stromal cells to a novel electrospun suture. (23rd April 2022) - Nezhentsev, Andrey; Abhari, Roxanna E; Baldwin, Mathew J; Mimpen, Jolet Y; Augustyniak, Edyta; Isaacs, Mark; Mouthuy, Pierre-Alexis; Carr, Andrew J; Snelling, Sarah J. B
Abstract: Background/Aims: Recurrent tears after surgical tendon repair remain common, with 40% of rotator cuff repairs failing within one year. Repair failures can be partly attributed to the use of sutures not designed for the tendon cellular niche nor designed for the promotion of repair processes. Clinically-used sutures have high tensile strength to mechanically support injured tendon. However, these sutures do not support cell integration into the material, but instead can stimulate a chronic inflammatory response. Synthetic electrospun materials can mechanically support the tendon while providing topographical cues that modulate the immune response to promote wound healing. Electrospun material has an increased surface area and porosity which can mimic that of tendon tissue, thus promoting tendon cell infiltration and proliferation. Here, a novel electrospun suture made from twisted polydioxanone (PDO) polymer filaments is compared to PDS II, a clinically used PDO suture currently utilised in tendon repair. Methods: We evaluated the ability of electrospun suture and PDS II to support the attachment and proliferation of human tendon-derived stromal cells using PrestoBlue cell viability assays and scanning electron microscopy. Suture surface chemistry was analysed using X-ray photoelectron spectroscopy. Bulk RNA-Seq interrogated the transcriptional response of primary tendon-derived stromal cells to sutures after 14 days. Results: The electrospun suture showed increased initial cell attachment compared to PDS II. X-ray photoelectron spectroscopy revealed that the local surface chemistry of electrospun suture and PDS II is similar, indicating that the tendon-like architecture of electrospun suture was responsible for the greater cell attachment. Furthermore, electrospun suture elicited a stronger transcriptional response compared with PDS II, with relative enrichment of pathways including mTorc1 signalling and depletion of epithelial-to-mesenchymal transition and extracellular matrix gene sets. When compared to baseline, neither suture induced transcriptional upregulation of inflammatory pathways such as IL6-JAK-STAT3 signalling and TNF-α signalling via NF-κB. Conclusion: Twisted electrospun sutures demonstrated a tendon-derived stromal cell response indicative of cell proliferation and wound healing, without significant fibrosis, when compared to clinically-used and safe PDS II suture. Twisted electrospun sutures therefore show promise in improving outcomes in surgical tendon repair by allowing increased cell attachment while maintaining an appropriate tissue response. Disclosure: A. Nezhentsev: None. R.E. Abhari: None. M.J. Baldwin: None. J.Y. Mimpen: None. E. Augustyniak: None. M. Isaacs: None. P. Mouthuy: None. A.J. Carr: None. S.J.B. Snelling: None.